Categorization of the water status of rice inoculated with arbuscular mycorrhizae and with water deficit = Categorización del estado hídrico del arroz inoculado con micorrizas arbusculares y con déficit hídrico - Ruiz Sánchez, Michel; Cabrera Rodríguez, Juan Adriano; Dell'Amico Rodríguez, José Miguel; Muñoz Hernández, Yaumara; Aroca Álvarez, Ricardo (2021)
Introduction. The water deficit negatively affects rice plants and limits their productivity. Arbuscular mycorrhizal symbiosis has been shown to improve rice productivity in drought conditions. Objective. To propose a new categorization for the state of water stress of rice plants inoculated (AM) or not with arbuscular mycorrhizal fungi (nonAM) and exposed to water deficit (D) during the vegetative phase. Materials and methods. The experiment was carried out under controlled greenhouse conditions during the years 2009 and 2010 at the Zaidín Experimental Station, Granada, Spain. The rice transplantation was carried out fourteen days after germination to pots with a 5 cm water sheet and at 30, 40, or 50 days after transplantation (DAT) they were subjected to water deficit during a period of 15 days, at which time the water sheet was restored. The control treatment was maintained throughout the cycle under flood conditions (ww). Evaluations were performed at 45, 55, 65 DAT and after recovery at 122 DAT. The harvest was carried out at 147 DAT. Results. The reduction in water supply demonstrated water stress in the plants, manifested by the decrease in the water potential of the leaves. Arbuscular mycorrhizal symbiosis always favored the water status of the plant. Four categories of water status of plants were proposed taking into account water potentials and agricultural yield: no stress (≥-0.67 MPa); light stress (<-0.67 to -1.20 MPa); moderate stress (<-1.20 to -1.60 MPa), and severe stress (<-1.60 MPa). Conclusion. The categorization of stress due to the water deficit is a tool of high scientific value for the specific case of rice, since this plant has the capacity to adapt to tolerate the presence of a sheet of water throughout its biological cycle and is highly susceptible to water deficit.
Introducción. El déficit hídrico afecta negativamente a las plantas de arroz y limita su productividad. Se ha demostrado que la simbiosis micorrízica arbuscular mejora la productividad del arroz en condiciones de sequía. Objetivo. Proponer una nueva categorización para el estado de estrés hídrico de las plantas de arroz inoculadas (MA) o no con hongos micorrízicos arbusculares (noMA) y expuestos al déficit hídrico (D) durante la fase vegetativa. Materiales y métodos. El experimento se llevó a cabo bajo condiciones controladas de invernadero durante los años 2009 y 2010 en la Estación Experimental del Zaidín, Granada, España. El trasplante del arroz se realizó catorce días después de la germinación a macetas con una lámina de agua de 5 cm y a los 30, 40 o 50 días después del trasplante (DAT) se sometieron a déficit hídrico durante un período de quince días, momento en que se restableció la lámina de agua. El tratamiento de control se mantuvo durante todo el ciclo en condiciones de inundación (ww). Las evaluaciones se realizaron a los 45, 55, 65 DAT y después de la recuperación a 122 DAT. La cosecha se efectuó a los 147 DAT. Resultados. La reducción del suministro de agua evidenció estrés hídrico en las plantas, manifestado por la disminución del potencial hídrico de las hojas. La simbiosis micorrízica arbuscular siempre favoreció el estado hídrico de la planta. Se propusieron cuatro categorías de estado hídrico de plantas teniendo en cuenta los potenciales hídricos y el rendimiento agrícola: sin estrés (≥-0,67 MPa); estrés ligero (<-0,67 a -1,20 MPa); estrés moderado (<-1,20 a -1,60 MPa) y estrés severo (<-1,60 MPa). Conclusión. La categorización del estrés debido al déficit hídrico es una herramienta de alto valor científico para el caso específico del arroz, ya que esta planta tiene la capacidad de adaptación para tolerar la presencia de una lámina de agua durante todo su ciclo biológico...
En Revista Agronomia mesoamericana--Volumen 32, número 2 (mayo-agosto 2021)--Descripción basada en el contenido visto el 21 de setiembre, 2023
También disponible en formatos EPUB, HTML y XML
Keywords: ARROZ -- INVESTIGACIONES -- ESPAÑA; RELACION PLANTA AGUA -- INVESTIGACIONES; SEQUIAS; MICORRIZAS; CULTIVOS DE SECANO; AGUA EN AGRICULTURA